Mudharabah in Islamic P2P Lending: A Critical Islamic Economics Perspective - Syafwendi Syafril; Firmansyah Shidiq Wardhana (Fakultas Ekonomi, UIN Maliki Malang, 2026)
This study analyzes the structural validity and Sharia compliance of mudharabah profit-sharing contracts used on Indonesian Islamic Peer-to-Peer (P2P) lending platforms. Using a qualitative normative legal approach, this study investigates the mudharabah contracts of two Sharia-compliant P2P platforms in Indonesia registered with the Financial Services Authority, Ammana.id and Qazwa.id. This study uses two benchmarks: the fatwas of the National Sharia Board of the Indonesian Ulema Council (DSN-MUI), and the Sharia standards of Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI), focusing on the absence of the guarantee of the capital, the uncertainty in profit, and the ambiguity in the loss. The findings show that there are two different methods of implementing mudharabah. Ammana.id employs a channeling agent model through Micro-Islamic Finance Institutions and maintains complete classical principles by exposing the investors to full financial risk and a profit distribution based on actual operating profit. On the other hand, Qazwa.id adopts a hybrid supply chain financing model, integrating mudharabah with murabahah contracts to enhance commercial viability, potentially undermining the fundamental equity-based risk-sharing character of mudharabah. Even though both platforms comply with the profit-sharing ratio provisions, the contradiction between Sharia authenticity and market viability, especially regarding capital loss allocation, persists. Most of the challenges are caused by the absence of sufficiently Sharia-compliant regulations on Fintech. This study is the first to systematically study the implementation of mudharabah contracts in Indonesian Islamic P2P lending and proposes a new analytical approach integrating classical contract parameters with Maqasid al-Sharia, coupled with proposals to improve some aspects of Islamic Fintech.